(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
One of the most important issues that an economic unit can face is changing accounting policies in light of the diversity of accounting options and alternatives, The aim of the study is to provide an introductory introduction to accounting policies and the impact of changes in accounting policies in accordance with the International Accounting Standard (IAS-2), Changing accounting policy is one of the most important issues that an economic unit can face, The important factors in improving the quality of accounting information in the financial statements through analyzing the relationship between the application of these policies and their accuracy and reliability, The research is based on an analytical study of the financial statements issued by the General Company for Textile and Leather Industries, The research reached a set of conclusions, the most important of which is that since the financial statements prepared by the company, whether based on manual or electronic programs, are not based on accurate information generated through the integrated system, their output does not truly indicate the efficiency and benefits of the company’s operations as a result of the company’s possession of a database, Unified and updated for all data related to the company’s branches, and in particular, with regard to the technical and statistical aspects. As a result of the use of old systems, it has become difficult to quickly and accurately obtain the necessary information as a result of the division and dispersion among the company’s departments, which has made it difficult to review the resulting financial statements, As for the recommendations, the most important of them is the need for all economic units to pay attention to the inventory component because it increases the ability of the economic unit to remain in the market and obtain many revenues for the economic unit